A STATEMENT OF OBJECTIVES OF THE AMERICAN ACCOUNTING ASSOCIATION. (The Accounting Review, 1936)
Abstract Accounting, originally designed for the purpose of providing internal control of business affairs by private owners, now finds itself faced with the responsibility of compiling and expressing the results of business operations in a way which will meet the needs of investors, governmental units, and the public at large, as well as those of the immediate management. The mechanism of private accounting must be adapted to serve these broad social and economic purposes. The best means of making this adaptation are not yet entirely clear. Alter a quarter century and more of active discussion and experimentation in this country, many of the simplest and most fundamental problems of accounting remain without an accepted solution. There is still no authoritative statement of essential principles available on which accounting records and statements may be based. It may be difficult to bring about an agreement as to what constitutes the only sound principle in any given case. It should not be difficult, however, to indicate in a general way the scope of the problem. This can be done best, perhaps, by stating a group of principles, which might be adopted as fundamental to sound accounting.